Development of Project Based Learning on Reaction Rate Material Using the Flipped Classroom With Moodle for Senior High School in Indonesia - Yani Yani Puspita; Muhammad Khairul Arif Bin Ahamad; Novri Wanda; Nadya Novera (Center For Advanced Material Processing, Artificial Intelligence, Biophys-Informatics (CAMPBIOTICS), Universitas Negeri Padang, 2021)
The development of information technology, the need for IT-based teaching, and learning concepts and mechanisms cannot be avoided. Therefore, a form of information is needed, in the form of a learning system facility called e-learning that can support the learning activities. This study aims to develop of e-learning based on project based learning on reaction rate material using the flipped classroom approach in Senior High School. This research is classified as Research and Development (R&D) using a 4-D development model. Populations in this research are students from Senior High School in West Sumatera, Indonesia. There are 20 Students of SMA N 8 Padang, in XI class level as respondents for developing this product. Research instruments used were interview sheet and validity and practicality questionnaires. Data showed that e-learning based on project based learning on reaction rate material through the flipped classroom was needed. The result of the validity sheet analysis with Aikens’s V showed the average score is 0,91 (for content validity) and 0,92 (for construct validity). The result of the practicality sheet analysis the average score is 0,83 (for practicality from students). Therefore, it can be concluded that e-learning based on project based learning on reaction rate material using the flipped classroom is valid and practical.